The handicraft in the law (2012)
Handicrafts are emblematic symbols of a nation, for which their socio- cultural connotation is rooted to the traditional authentic knowledge and to the regional customs that both produce. This includes intangibles rights, which deserve to be legally protected, in order to facilitate their development as a true economic sector. In this framework, in Colombia, it is most common to protect these goods by using the Collective Trademark and Copyright. However, the appellations of origin not only are an ideal figure that brings protection to both, the handicrafts and their creators, but also promote the cultural identity of a country worldwide.